RESVERATROL 10C-GLUKOPIRANOSIDA DAN HEIMIOLA, KARAKTER Hopea gregaria SECARAKEMOTAKSONOMI - Sahidin Sahidin; EH Hakim; YM Syah; LD Juliawaty; SA Achmad; LB Din; J Latip (BERITA BIOLOGI, 2008)
Ten resveratrol oligomers have been isolated from the stem bark of H. gregaria i.e. resveratrol lOC-glucopyranoside (1), heimiol A (2), balanocarpol (3), ampelopsin A (4), hopeaphuran (5), E-viniferin (6), parviflorol (7), a-viniferin (8), hopeaphenol (9), and vaticanoi B (10). The structures of these compounds were determined base on spectroscopic methods including UV, IR, 1-D NMR, 2-D NMR and comparison with the reported data. Implication of the compounds invention is not only strengthen conclusion that Hopea tends to produce resveratrol dimmers but also showed that resveratrol lOC-glucopyranoside (1) and heimiol A (2) are phytochemical markers of. H. gregaria.